The Interplay of Global Governance with Domestic and Local Access: Insights from the FLEGT VPAs in Ghana and Indonesia. Issue 2 (1st February 2020) - McDermott, Constance L.; Hirons, Mark; Setyowati, Abidah
Abstract: This article examines the EU FLEGT Voluntary Partnership Agreements (VPAs) with Ghana and Indonesia to explore how scale and sources of authority shape access to forest resources. VPAs require the development of internationally recognized legality verification systems to eliminate trade in illegal wood and thus aim to reinforce state law while opening it to broader national and international scrutiny. Analysis of relevant documents, combined with over 70 stakeholder interviews at local to international scales reveal significant differences between Ghana and Indonesia in the design of their verification systems and the attention given to local and domestic forest access. Yet in both countries, a strong focus on legality verification, coupled with a lack of key governance reforms, favors international trade over local access. This calls into question the EU's growing legality agenda and highlights the need for alternative approaches to reforming domestic resource governance that are more appropriate and beneficial for local forest users.